(3QSGdI aj GdOhdI GdMSfjIs - (3GdSfhSj , eMeO Hf Ydj Hf GdSfhSj, CHh YHO Gddg,J (B1276 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CYR Ojfg hHYO aEf GdSdWGf ehdGfG GdMSf Hf GdSWGf ehdGfG eMeO deG hdi GdNdGaI GdaUd GdChd ai HjGf eYfi GdeUGdM s
(3BNQgG (B:s
(3bjd fGjH GdfHi dg ef GdMbhb eG ddfHi hdh JJHYfG aUd Gdedhc hCQ OYhGfG Cf GdMeO ddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cGf GdaQGZ ef JCdjag YGe (B1299 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B14s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs